Spinal Arachnoiditis Ossificans: A Case-Based Update - Brunner, Anna; Leoni, Marlene; Eustacchio, Sandro; Kurschel-Lackner, Senta (The Surgery Journal, 2021)
Arachnoiditis ossificans is a rare disease, characterized by intradural ossifications, representing the end stage of chronic adhesive arachnoiditis. We describe the case of a 55-year-old patient who developed symptoms of a cauda equina syndrome after an open microdiscectomy at the L5 to S1 segment. A subsequent exploratory surgery revealed an intradural concentric bony structure with partly incorporated and partly adherent nerve roots. A partial removal of the intradural calcifications was performed. Postoperatively, the patient showed neurological improvement. The removed intradural calcifications were submitted for histological analysis and proved to be normal bone tissue, notably containing yellow bone marrow. To our knowledge, the presence of yellow bone marrow within bony cavities of arachnoiditis ossificans has not previously been reported.
Keywords: arachnoiditis ossificans; spinal surgery; yellow bone marrow; cauda equina syndrome